The Effectiveness of the ABCDE Technique in Rational Emotive Behavior Therapy to Increase Self-Confidence of Victims of Verbal Bullying: Literature Review - Riesya Intan Syarafina; Meidina Mahmudatus Sholikhah; Nasywa Azrelianova; Damajanti Kusuma Dewi (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Verbal bullying is a serious problem that affects an individual's psychological health and psychosocial development, especially in terms of self-confidence. Victims often internalize ridicule or insults as absolute truths, forming irrational thought patterns that trigger low self-esteem, anxiety, and withdrawal from social environments. This article reviews 10 nationally and internationally accredited literature published in the period 2020–2025 to examine the effectiveness of Rational Emotive Behavior Therapy (REBT) in increasing the self-confidence of victims of verbal bullying. The results of the review show that REBT is able to change irrational beliefs into more logical, realistic, and adaptive rational ones. This cognitive restructuring process contributes to increased self-acceptance, positive emotions, and victims' courage in social interactions. The most influential stages in the ABCDE model are Disputation (D) and Effective new belief (E), as both help victims challenge negative thoughts and form new, healthier beliefs so that self-confidence can be restored. Further research suggestions include exploring the application of REBT in a group counseling format, assessing its long-term effectiveness through a longitudinal design, and integrating contextual factors such as culture, social support, and school environment, so that interventions for victims of verbal bullying can be more comprehensive and applicable.